2018
DOI: 10.1055/s-0043-123463
|View full text |Cite
|
Sign up to set email alerts
|

Prenatally Diagnosed Single Umbilical Artery (SUA) – Retrospective Analysis of 1169 Fetuses

Abstract: Once fetal SUA is diagnosed, intense sonoanatomy of the fetus is required and, if associated malformations are found, genetic testing must be offered. In iSUA intermittent biometry is recommended for the early detection of IUGR but additional genetic testing is not necessarily recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 28 publications
(38 reference statements)
2
35
1
1
Order By: Relevance
“…In 60 children (5.1%), chromosomal or structural anomalies were detected postpartum. 68 Isolated single umbilical artery was also noted in another study to be an independent predictor of adverse perinatal outcomes in term neonates. In this study, isolated single umbilical artery was noted in 786 (0.3%) of 233,123 deliveries.…”
Section: Possible Confounding Factors Single Umbilical Arterymentioning
confidence: 79%
See 1 more Smart Citation
“…In 60 children (5.1%), chromosomal or structural anomalies were detected postpartum. 68 Isolated single umbilical artery was also noted in another study to be an independent predictor of adverse perinatal outcomes in term neonates. In this study, isolated single umbilical artery was noted in 786 (0.3%) of 233,123 deliveries.…”
Section: Possible Confounding Factors Single Umbilical Arterymentioning
confidence: 79%
“…7,67 Friebe-Hoffmann et al detailed a retrospective analysis of 1169 women with singleton pregnancies diagnosed with single umbilical artery. 68 Of the 169 fetuses, 989 (84.6%) were noted to have an isolated single umbilical artery while 180 (15.4%) presented with additional structural and/or chromosomal anomalies. Fetuses with single umbilical artery had lower birth weight (2825 grams versus 3220 grams, P<0.00) and higher rates of preterm delivery before 34 weeks' gestation (13.7% versus 3.8%, P<0.001), and weighed <5th centile (21.6% versus 9.3%, P<0.001).…”
Section: Possible Confounding Factors Single Umbilical Arterymentioning
confidence: 99%
“…Friebe-Hoffmann et al demonstrated that 5.1% of neonates born with an isolated single umbilical artery had been delivered preterm (15). Others have reported a preterm rate of 11.8% (16).…”
Section: Discussionmentioning
confidence: 99%
“…Die fetale singuläre Nabelschnurarterie tritt mit einer Inzidenz von etwa 0,5 % auf [14,15]. Die retrospektive Analyse von allen Feten mit einer singulären Umbilikalarterie (SUA), die in einer großen pränatalmedizinischen Praxis diagnostiziert wurden, ergab interessante Erkenntnisse [15]: Über einen Zeitraum von 7 Jahren fand sich bei 1169 Schwangeren mit Einlingen eine SUA (▶ Abb. 10).…”
Section: Häufige Anomalie Fetaler Umbilkalgefäße: Singuläre Umbilikalunclassified